CODE SWITCHING USED BY NIKI ON THE VIDEO NGOBROL BARENG NIKI: YANG DIRINDUKAN DARI INDONESIA BY NAJWA SHIHAB: A SOCIOLINGUISTIC STUDY - Fikri Fauzi, Deri; Maulida Utami, Nurfajri (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2023)
Language is an important aspect for humans to communicate. The study that discusses the relationship between society and language is called sociolinguistics. In sociolinguistics, there is a phenomenon called bilingualism. Bilingualism is the ability of a speaker to use two languages and it is a common phenomenon in multilingual societies and this phenomenon is associated with code-switching. Code-switching refers to the practice of altering one’s language or language variety in different social or cultural contexts. This phenomenon happened in Najwa Shihab’s YouTube video entitled Ngobrol bareng NIKI: Yang dirindukan dari Indonesia. Therefore, this research aims to analyse the code switching used by Niki in her interview with Najwa Shihab. The purpose of this research is to describe the main types of code-switching used by Niki in her interview and to describe the reason why Niki switched one language to another in her interview. This research used a descriptive qualitative method. In collecting the data, the writer transcribed the utterance from the video to get the data. In analysing the data, Poplack’s theory was used to analyse the types of code-switching and Hoffmann’s theory were used to analyse the reasons for code-switching. After analysing the data, there was 53 data found for types of code-switching and 38 data found for code-switching reasons. For the types, tag-switching was found to be the main type that Niki used in her interview and for the reasons, talking about particular topics and intention of clarifying the speech content for the interlocutor was found to be the main reasons why Niki used code-switching.